2010
DOI: 10.1007/s10658-010-9662-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of potential resistance inducers on development of Microdochium majus and Fusarium culmorum in winter wheat

Abstract: The effect of potential resistance inducing chemicals on disease development of Fusarium head blight was studied in winter wheat (Triticum aestivum L.). As a pre-screening test, the effect of different treatments on development of Microdochium majus (syn. Microdochium nivale var. majus) was studied in detached leaves. Based on these tests, DL-3-aminobutyric acid, Bion (benzo-(1,2,3) thiadiazole-7-carbothioic acid S-methyl ester), and a foliar fertilizer containing potassium phosphite were selected for further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
0
15
0
3
Order By: Relevance
“…Thus, with this practice, we observed a growth decrease of Alternaria alternata (Reuveni et al, 2003), Colletotrichum gloeosporioides (Araujo et al, 2010), Fusarium culmorum and F. graminearum (Hofgaard et al, 2010) …”
Section: Direct Actionmentioning
confidence: 68%
See 3 more Smart Citations
“…Thus, with this practice, we observed a growth decrease of Alternaria alternata (Reuveni et al, 2003), Colletotrichum gloeosporioides (Araujo et al, 2010), Fusarium culmorum and F. graminearum (Hofgaard et al, 2010) …”
Section: Direct Actionmentioning
confidence: 68%
“…Así, mediante esa práctica se reportó disminución en el crecimiento de Alternaria alternata (Reuveni et al, 2003), Colletotrichum gloeosporioides (Araujo et al, 2010), Fusarium culmorum y F. graminearum (Hofgaard et al, 2010), Mycosphaerella digitatum (Cerioni et al, 2013), Phytophthora cinnamomi (Wilkinson et al, 2001;Won et al, 2009;King et al, 2010), P. cinnamomi, P. palmivora and P. nicotianae (Smillie et al, 1989), P. infestans (Bórza et al, 2014), P. plurivora (Dalio et al, 2014) and Pythium aphanidermatum, P. ultimum, P. irregulare, P. myriotylum, P. torulosum, P. volutum and P. graminicola (Cook et al, 2009). The decrease level in the microorganisms' growth as a consequence of the phosphite ion is determined by the organism tested, amount of phosphite added to the culture medium, type of ion bonded to phosphite and pH produced by the culture medium (Lobato et al, 2010).…”
Section: Acción Directamentioning
confidence: 98%
See 2 more Smart Citations
“…And Walters et al, [31] demonstrated the effectiveness of potassium phosphiteto control different diseases, including those caused by Phytophthora infestans, Fusarium oxysporum and Rhizoctonia solani. It was found that the foliar application of potassium phosphite reduced by 40% the severity of wheat wilt caused by F. culmorum [32].…”
Section: Introductionmentioning
confidence: 99%